REKOMENDASI TIM ASESMEN TERPADU YANG BERPERAN UNTUK PROSES REHABILITASI BAGI PENYALAHGUNA NARKOTIKA (Studi di BNNP Jawa Timur) - Aji Pratama, Wisnu (Cahaya Ilmu Bangsa, 2025)
Drug abuse is a complex issue with widespread impacts on health, society, and law enforcement. Indonesia has implemented a rehabilitation policy for drug addicts under Law No.35 of 2009 on Narcotics, emphasizing a dual-track approach involving both criminal sanctions and rehabilitation. One of the key instruments in this policy is the Integrated Assessment Team (Tim Asesmen Terpadu - TAT), which evaluates the legal and medical status of drug abusers to determine rehabilitation recommendations. This study employs an empirical juridical method with a socio-legal and statutory approach, including interviews with the TAT Secretariat staff of the East Java National Narcotics Agency and literature studies. The findings indicate that the implementation of TAT still faces challenges in inter-agency coordination and overall effectiveness. Therefore, further evaluation and regulatory strengthening are necessary to ensure that rehabilitation policies effectively address drug abuse in Indonesia.